Vibrational Spectroscopy and Dynamics of Water - Perakis, Fivos; De Marco, Luigi; Shalit, Andrey; Tang, Fujie; Kann, Zachary R.; Kühne, Thomas D.; Torre, Renato; Bonn, Mischa; Nagata, Yuki (Chemical Reviews, 2016)
We present an overview of recent static and time-resolved vibrational spectroscopic studies of liquid water from ambient conditions to the supercooled state, as well as of crystalline and amorphous ice forms. The structure and dynamics of the complex hydrogen-bond network formed by water molecules in the bulk and interphases are discussed, as well as the dissipation mechanism of vibrational energy throughout this network. A broad range of water investigations are addressed, from conventional infrared and Raman spectroscopy to femtosecond pump-probe, photon-echo, optical Kerr effect, sum-frequency generation, and two-dimensional infrared spectroscopic studies. Additionally, we discuss novel approaches, such as two-dimensional sum-frequency generation, three-dimensional infrared, and two-dimensional Raman terahertz spectroscopy. By comparison of the complementary aspects probed by various linear and nonlinear spectroscopic techniques, a coherent picture of water dynamics and energetics emerges. Furthermore, we outline future perspectives of vibrational spectroscopy for water researches.
CRIS-Team Scopus Importer:2023-03-20